2017
DOI: 10.1111/1475-6765.12233
|View full text |Cite
|
Sign up to set email alerts
|

Partisan effects in morality policy making

Abstract: Current comparative policy research gives no clear answer to the question of whether partisan politics in general or the partisan composition of governments in particular matter for different morality policy outputs across countries and over time. This article addresses this desideratum by employing a new encompassing dataset that captures the regulatory permissiveness in six morality policies that are homosexuality, same‐sex partnership, prostitution, pornography, abortion and euthanasia in 16 European countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The strand of research focusing on the role of political parties in morality policymaking has found that ideological colour affects policy change. While left and secular parties tend to support liberal values and promote SSU regulation (Budde et al 2017), conservative and confessional parties tend to oppose and block the country's path towards permissiveness in morality policy (Engeli, Green-Pedersen and Larsen 2013). Other studies have addressed the relevance of congruence in issue positions within the government coalition (Varone, Rothmayr and Montpetit 2006); this means that in the case of substantial disagreement between government actors, a process of nondecision or postponement is likely to occur.…”
Section: Morality Issues At Stake: Explaining the Variety Of Ssu Regulation In Europementioning
confidence: 99%
“…The strand of research focusing on the role of political parties in morality policymaking has found that ideological colour affects policy change. While left and secular parties tend to support liberal values and promote SSU regulation (Budde et al 2017), conservative and confessional parties tend to oppose and block the country's path towards permissiveness in morality policy (Engeli, Green-Pedersen and Larsen 2013). Other studies have addressed the relevance of congruence in issue positions within the government coalition (Varone, Rothmayr and Montpetit 2006); this means that in the case of substantial disagreement between government actors, a process of nondecision or postponement is likely to occur.…”
Section: Morality Issues At Stake: Explaining the Variety Of Ssu Regulation In Europementioning
confidence: 99%
“…In particular, social democratic and other centre-left parties in Europe traditionally have been more supportive of gender and LGBTI rights than the parties of the centre-right such as the Christian Democratic parties that seek to uphold more traditionalist values (Engeli et al 2012;Badgett 2009). While findings on this indicator are mixed (Siegel & Wang 2018;Budde et al 2018), we assume that countries where centre-left parties have been in government more often will be more likely to expand LGBTI rights.…”
Section: Alternative Hypothesesmentioning
confidence: 99%
“…On balance, however, in both the US and Europe evidence for partisanship as a driver of government spending or other policy outcomes is highly conditional (Baumgartner et al, 2009; Bevan and Greene, 2016; Budde et al, 2018; Froio et al, 2017; McAtee et al, 2003; McManus, 2019). Political parties are obviously important, so these results are surprising.…”
Section: Partisanship and Policy Outcomesmentioning
confidence: 99%